Career Development, Motivation and Promotion on Employee Performance - Novita Wahyu Setyawati; Dewi Sri Woelandari PG; Muhammad Richo Rianto (East Asian Journal of Multidisciplinary Research, 2022)
The performance itself is the result in quality and quantity achieved by employees in carrying out the duties and responsibilities authorized to them. If the performance of a company is not good, then the company will experience a setback in the existing competition. Humans are assets for companies that must be directed and guided to have the ability according to the desired expectations, integrity, loyalty and high morale need to be applied to employees to have a sense of responsibility for the work discipline, motivation and job satisfaction they do. Poor work discipline, motivation and job satisfaction can cause various problems in a company, such as employee performance. This study aims to determine whether career development, motivation, promotion affect employee performance. The method used is the PLS method. Based on the results of research and discussion, it can be concluded that: the latent variables of career development, motivation and promotion have t-statistic values of 2.012, 3.038, and 4.485 > 1.96 and have p-values of 0.045, 0.003, and 0.000 < 0.05. So it can be said that the latent variable of career development, motivation, and promotion have a significant effect on employee performance.